2003
DOI: 10.1124/jpet.103.060186
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of Carbon Monoxide and Metabotropic Glutamate Receptor Groups in the Nucleus Tractus Solitarii of Rats

Abstract: Carbon monoxide has been shown to act as a neurotransmitter and neuronal messenger in the brain. Heme oxygenase catalyzes the conversion of heme to carbon monoxide and biliverdin. We have recently reported that carbon monoxide was involved in central cardiovascular regulation. Carbon monoxide modulated the baroreflex and may affect glutamatergic neurotransmission. In addition, metabotropic glutamate receptors may be coupled to the activation of heme oxygenase in the nucleus tractus solitarii of rats. The prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 35 publications
2
17
0
Order By: Relevance
“…Fourth, the mGluR antagonist CPPG blocks responses to L-AP4 but is without effect on responses to NMDA or AMPA (54). Fifth, as discussed in detail later in the DISCUSSION, recent evidence indicates that L-AP4 but not NMDA produces its actions in NTS, at least in part, via the release of CO, which in turn may increase glutamate release (34,35). These data suggest that CO production may be an intermediary step by which L-AP4 enhances NMDA-mediated transmission without directly activating the NMDA receptor (34,35).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Fourth, the mGluR antagonist CPPG blocks responses to L-AP4 but is without effect on responses to NMDA or AMPA (54). Fifth, as discussed in detail later in the DISCUSSION, recent evidence indicates that L-AP4 but not NMDA produces its actions in NTS, at least in part, via the release of CO, which in turn may increase glutamate release (34,35). These data suggest that CO production may be an intermediary step by which L-AP4 enhances NMDA-mediated transmission without directly activating the NMDA receptor (34,35).…”
Section: Discussionmentioning
confidence: 99%
“…Fifth, as discussed in detail later in the DISCUSSION, recent evidence indicates that L-AP4 but not NMDA produces its actions in NTS, at least in part, via the release of CO, which in turn may increase glutamate release (34,35). These data suggest that CO production may be an intermediary step by which L-AP4 enhances NMDA-mediated transmission without directly activating the NMDA receptor (34,35). Finally, the results of the present study, discussed below, suggest that the cardiovascular effects of L-AP4 microinjection in the NTS are not mediated by L-AP4 or glycine contaminants acting at the glycine site on NMDA receptors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The neural effects of heme oxygenase are generally different from those of nitric oxide (NO) synthase (23). Recent studies have demonstrated that CO is involved in central cardiovascular regulation and modulates the baroreflex in the nucleus tractus solitarii of rats (24,25). The present study investigated the possible role of ACPC in the regulation of HO-1 expression and antioxidant effects in stroke-prone spontaneously hypertensive rats (SHRSP).…”
Section: Introductionmentioning
confidence: 94%